The mediator effect of financial performance on the relationship between board of directors’ size and corporate social responsibility disclosure: a case study of Palestinian listed companies - Omar Tarda; Hasnah Haron; Nathasa Ramli; Supiah Salleh (Cogent Economics & Finance, 2024)
The Board of Directors (BOD) is responsible for making strategic decisions within a company and holds significant influence over corporate social responsibility (CSR) policies and their disclosure. Furthermore, financial performance plays a vital role in this relationship, as a strong financial performance can impact a company’s ability to allocate resources towards social responsibility and, consequently, affect its CSR disclosure. The previous studies have not examined financial performance as a mediating variable between BOD size and CSR disclosure. This article aims to examine the level of CSR disclosure in Palestine, analyze the impact of BOD size on CSR disclosure and financial performance, and assess the extent to which financial performance acts as a mediating variable between BOD size and CSR disclosure. The study employs panel data analysis using a sample of 31 companies listed on the Palestine Stock Exchange from 2012 to 2021. The Baron and Kenny approach will be used to examine the mediating effect of financial performance between BOD size and CSR disclosure. The theoretical framework of resource dependence theory will be adopted to understand the relationship between the variables under investigation. The results of this study reveal that the CSR disclosure rate was 29.5% among the companies included in the sample. Additionally, the results show a significant positive direct relationship between BOD size, CSR disclosure, and financial performance. Furthermore, the results indicate that financial performance partially mediates the association between BOD size and CSR disclosure in Palestinian companies.